Infiltration of colorectal carcinoma by S100+ dendritic cells and CD57+ lymphocytes as independent prognostic factors after radical surgical treatment - Liska, Vaclav; Vycital, Ondrej; Daum, Ondrej; Novak, Petr; Treska, Vladislav; Bruha, Jan; Pitule, Pavel; Holubec, Lubos (Anticancer research, 2012)
BACKGROUND: S100(+) dendritic cells and CD57(+) lymphocytes are factors reflecting the immune system's ability to suppress the progress of tumor growth. CD57(+) cells include natural killer cells and late stages of T-effector lymphocytes. We evaluated the relationship between the known clinical and histological factors and tumor markers as well as the presence of S100(+) and CD57(+) cells in the tissue of colorectal carcinoma with the aim of detecting patients at high risk of short overall survival (OS) or short disease-free interval (DFI) after radical surgical treatment and we further analyzed whether S100(+) and CD57(+) positivity could bring on new information regarding the treatment regimen. MATERIALS AND METHODS: Data of 150 patients (97 males and 53 females) that underwent an elective radical surgical procedure for colorectal cancer were studied. The influence on DFI and on OS of the following parameters was evaluated: grading, staging and positivity for S100 and CD57 by immunohistochemical staining. We also analyzed the relation of preoperative serum levels of the tumor markers Carcinoembryonic Antigen (CEA), Cancer Antigen 19-9 (CA19-9), Cancer Antigen 72-4 (CA72-4), Thymidine kinase (TK), Tissue-Specific Polypeptide Antigen (TPS) and Tissue Polypeptide Antigen (TPA) in relation to S100 and CD57 positivity/negativity for the same patients. RESULTS: OS at 1, 3 and 5 years was 92.2%, 76.5% and 70.2%; the DFI at 1, 3 and 5 years was 85.3%, 64.3% and 49.4%. CD57 positivity in the tumor mass was proven as a positive prognostic factor for OS. Risk of short OS was 2.5-fold higher in patients with low tumor infiltration by CD57(+) lymphocytes. The combination of N2 stage for lymph nodes and the absence of CD57(+) cells was proven to be the strongest negative prognostic factor for OS. No significant influence of CD57 positivity on DFI appeared. There was no significant influence of S100 positivity on OS or DFI; nor was there any statistical dependence of CD57 and S100 positivity or negativity on preoperative serum levels of CEA, CA19-9, CA72-4, TK, TPS or TPA. Both studied factors were shown to be statistically independent factors. CONCLUSION: The present study showed infiltration of colorectal cancer tissue by CD57(+) cells as being an important independent positive prognostic factor for OS.
Keywords: CD57 Antigens; Humans; T-Lymphocytes; dendritické buňky; Biomarkers, Tumor; Female; Aged; senioři; lidé; nádorové biomarkery; staging nádorů; S100 Proteins; ženské pohlaví; kolorektální nádory; Male; Dendritic Cells; antigeny CD57; prognóza; T-lymfocyty; Neoplasm Staging; mužské pohlaví; Prognosis; Colorectal Neoplasms; proteiny S100